The exploring the role of Balinese gamelan in shaping tourist experiences and tourism growth in Bali - Dwipayana, I Kadek Wisnu; Wajdi, Majid; Sutiarso, M. Agus; Zulfan, Muhammad; Aruku, Kalita Joseph (Yayasan Mitra Persada Nusantara, 2025)
Balinese Gamelan, as a key aspect of Balinese culture, significantly influences cultural tourism and tourist visits. This research analyzes how gamelan, an integral part of Balinese religious rituals and celebrations, contributes to a unique tourist experience. By incorporating elements such as local wisdom, cultural preservation, and the creative economy, the study shows that gamelan performances serve not only as entertainment but also as a means to introduce and preserve local traditions for visitors. Using a qualitative approach, data was collected through interviews with gamelan musicians, and tourists, along with direct observations at various cultural events. The results indicate that tourists' involvement in gamelan experiences enhances their understanding of Balinese culture and strengthens the values of cultural preservation. The research concludes that gamelan is not just a tourist attraction, it also plays an essential role in supporting sustainable tourism and raising awareness about the importance of maintaining cultural heritage in the modern era.